Binding and transcriptional activation by Uga3p, a zinc binuclear cluster protein of Saccharomyces cerevisiae redefining the UAS [subscript GABA] and the Uga3p binding site,Binding and transcritional activation by Uga3p, a zinc binuclear cluster protein of Saccharomyces cerevisiae : redefining the UASGABA and the Uga3p binding site - Idicula, Anu Mary (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2003)
Uga3p, a member of the zinc binuclear cluster transcription factor family, is required for [gamma]-aminobutyric acid-dependent transcription of the UGA genes in Saccharomyces cerevisiae. Crystallographic data of some of the protein-DNA complexes of this family reveal that members of this family bind to CGG triplets. A conserved 19-nucleotide activation element in certain UGA gene promoter regions contains a CCG-N4-CGG everted repeat, proposed to be the binding site of Uga3p, UAS[subscript GABA]. The spacer region (N4) between the CGG triplets has been suggested to be the specificity determinant for binding to UAS[subscript GABA]. The data available from the Saccharomyces genome database indicates that there are multiple repeats of -CCG-N4-CGG- regions within the genome. These transcription factors are involved in the activation of specific pathways and the question arises as to how their specificity of binding is determined. The aim of this study was to understand the binding characteristics of Uga3p to UAS[subscript GABA] and to determine the affinity and specificity of this interaction. In this study, full-length (tagged and untagged) and truncated (1-124 a.a.) Uga3p was produced in a heterologous expression system (E. coli). The interaction of Uga3p with UAS[subscript GABA] in Saccharomyces cerevisiae was characterized in terms of binding in vitro and the transcriptional activation of lacZ reporter genes in vivo. The Uga3p was capable of binding to these sites in vitro independent of exogenous GABA. Electrophoretic mobility shift assays (EMSA) of the full-length Uga3p with the wild type UAS[subscript GABA] sequences produced two distinct mobility complexes. The complexes formed in the EMSA of the full-length Uga3p were those specific to the interaction of the Uga3p to UAS[subscript GABA]. The truncated Uga3p(1-124 a.a.), which has the DNA-binding zinc cluster domain, the linker region and the putative coiled-coil domain was not functionally equivalent to the full-length protein with respect to binding in vitro because the EMSAs of the UAS[subscript GABA] with the truncated Uga3p produced indistinct complexes. EMSAs using mutant UAS[subscript GABA] sequences and heterologously-produced full-length Uga3p, demonstrated that UAS[subscript GABA] consists of two, independent Uga3p-binding sites. This work presents evidence that the two Uga3p molecules bound to UAS[subscript GABA] most likely interact with each other. Unlike other zinc cluster binding sites the Uga3p-binding site is an asymmetric site of 5'-SGCGGNWWT-3' (S= G or C, W = A or T and N = no nucleotide or G or C). UAS[subscript GABA] is a palindrome containing the two asymmetric Uga3p-binding sites. The two-site consensus sequence required for the binding of Uga3p to the UAS[subscript GABA] is present upstream of UGA1 (region -387 to -370) and UGA4 (region -403 to -387). Furthermore, a single Uga3p-binding site was identified in the 5' untranslated regions of UGA2 (region -219 to -211). GABA-dependent transcriptional activation by UAS[subscript GABA] in vivo could be directly correlated to a high affinity, specific interaction of two Uga3p molecules to this UAS. Binding with high affinity required the conserved sequences flanking the everted repeat. This study provided evidence that the binding pattern of Uga3p is novel compared to other zinc cluster motifs investigated, as the sequences flanking the everted repeat are important regions for recognition by Uga3p. The studies with the truncated Uga3p (1 "“124 a.a.), also suggested that the regions C-terminal to the DNA-binding motif and putative coiled-coil area of this protein are important for Uga3p-specific interactions with UAS[subscript GABA]. Investigation of regions C-terminal to the zinc cluster, linker and putative coiledcoil revealed an eight-motif regulatory region similar to that in other zinc cluster proteins. This indicated that the regions C-terminal to these domains are important for the regulation and activity of these proteins. A putative seven repeat WD40-like motif was identified within this region. This putative domain has been speculated to be important for protein-protein interactions. Phosphorylation and dephosphorylation in other proteins of this class have been indicated to be important for the regulation of the activity of these proteins. The bioinformatic analysis of Uga3p revealed two possible cAMP/cGMP-dependent protein kinase phosphorylation sites, four putative protein kinase C phosphorylation motifs and four putative casein kinase II phosphorylation motifs. This study has contributed to the understanding of the nature of interactions between Uga3p and its specific UAS [subscript GABA] and how the regions flanking the everted repeat determine its specificity. The comparison of the nature of the binding of truncated and full-length Uga3p in vitro provided evidence for the role played by the full-length protein in determining this specific interaction. This evidence suggested that the in vitro binding evidence for other proteins of this family, using truncated peptides that carry the DNA-binding domain, might not reflect the true nature of interactions between the proteins of this class and their specific UASs in vivo.
Keywords: Saccharomyces cerevisiae; GABA